Early maternal experience shapes offspring performance in the wild. Issue 3 (1st March 2013) - Burton, Tim; McKelvey, S.; Stewart, D. C.; Armstrong, J. D.; Metcalfe, N. B.
Abstract : Both the environments experienced by a mother as a juvenile and an adult can affect her investment in offspring. However, the implications of these maternal legacies, both juvenile and adult, for offspring fitness in natural populations are unclear. We investigated whether the juvenile growth rate and adult reproductive traits (length, body condition, and reproductive investment at spawning) of female wild Atlantic salmon ( Salmo salar ) were related to the growth and survival of their offspring. Adult salmon captured on their upstream migration were used to create experimental full‐sib clutches of eggs, which were mixed and then placed in artificial nests in a natural stream that lacked salmon due to a migration barrier. Four months later we resampled the stream to obtain family‐level estimates of offspring size and survival. Mothers that had grown slowly as juveniles (as determined by scalimetry) but had invested heavily in reproduction (egg production for a given body length) and were in relatively poor body condition (somatic mass for a given body length) at spawning produced the largest eggs. Larger eggs resulted in larger juveniles and higher juvenile survival. However, after controlling for egg size, offspring growth was positively related to maternal juvenile growth rate and reproductive investment. The predictors of offspring survival (i.e., reproductive success) varied with the juvenile growth rate of the mother: If females grew slowly as juveniles, their reproductive success was negatively related to their own body condition. In contrast, the reproductive success of females that grew quickly as juveniles was instead related positively to their own body condition. Our results show that maternal influences on offspring in the wild can be complex, with reproductive success related to the early life performance of the mother, as well as her state at the time of breeding.